Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$\lim_{x\to\infty}{(x-2)^2\over2x+1}=\dfrac{1}{2}$$ I used an online calculator and it said it was actually $=\infty$

Here's how I calculate it: $$\lim_{x\to\infty}\dfrac{x^2+4-4x}{2x+1}=\lim_{x\to\infty}\dfrac{({x\over x}-{2\over x})({x\over x}-{2\over x})}{({2x\over x}+{1\over x})}=\dfrac{(1-0)(1-0)}{(2+0)}={1 \over 2}$$

share|improve this question
    
You have divided the numerator by $x^2$, but the denominator only by $x$. –  Daniel Fischer Apr 7 at 10:39
    
What do you mean? I divided both numerator and dneominator by x –  Mouse Hello Apr 7 at 10:40
    
No, $$(x-2)^2 = (x-2)(x-2) = \left[x\left(\tfrac{x}{x}-\tfrac{2}{x}\right)\right]\cdot\left[x\left(\tfrac{x}{‌​x}-\tfrac{2}{x}\right)\right] = x^2\left(\tfrac{x}{x}-\tfrac{2}{x}\right)\left(\tfrac{x}{x}-\tfrac{2}{x}\right).‌​$$ –  Daniel Fischer Apr 7 at 10:43
2  
@DanielFischer are you going to write it as an answer? –  Mouse Hello Apr 7 at 10:45

2 Answers 2

up vote 6 down vote accepted

You have accidentally divided the numerator by $x^2$ and the denominator only by $x$. For the numerator we get

$$(x-2)^2 = \left[x\left(\tfrac{x}{x}-\tfrac{2}{x}\right)\right]\cdot \left[x\left(\tfrac{x}{x}-\tfrac{2}{x}\right)\right] = x^2\left(1-\tfrac{2}{x}\right)^2,$$

so the fraction is

$$\frac{(x-2)^2}{2x+1} = \frac{x^2\left(1-\tfrac{2}{x}\right)^2}{x\left(2+\frac{1}{x}\right)} = \underbrace{x}_{\to\infty}\underbrace{\frac{\left(1-\tfrac{2}{x}\right)^2}{\left(2+\frac{1}{x}\right)}}_{\to \frac{1}{2}}.$$

share|improve this answer

The online calculator is correct. The value of the limit $\to\infty$. Here is the proof: $$ \begin{align} \lim_{x\to\infty}{(x-2)^2\over2x+1}&=\lim_{x\to\infty}\frac{x^2-4x+4}{2x+1}\\ &=\lim_{x\to\infty}\frac{x^2-4x+4}{2x+1}\cdot\frac{\frac{1}{x}}{\frac{1}{x}}\\ &=\lim_{x\to\infty}\frac{\frac{x^2}{x}-\frac{4x}{x}+\frac{4}{x}}{\frac{2x}{x}+\frac{1}{x}}\\ &=\lim_{x\to\infty}\frac{x-4+\frac{4}{x}}{2+\frac{1}{x}}\\ &=\frac{\left(\lim\limits_{x\to\infty}x\right)-4+0}{2+0}\to\boxed{\Large\color{blue}{\infty}}\\ \end{align} $$

$$\\$$


$$\Large\color{blue}{\text{# }\mathbb{Q.E.D.}\text{ #}}$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.